'The map that would save Europe': Clive Morrison-Bell, the Tariff Walls Map, and the politics of cartographic display - Heffernan, Mike; Thorpe, Benjamin J. (Elsevier, 2018)
This essay uses the personal archives of Clive Morrison-Bell (1871-1956), a campaigning Conservative politician who made extensive use of maps and cartographic models, to consider the entangled histories of cartography, economics and geopolitics in early twentieth-century Britain. Particular attention is paid to Morrison-Bell’s Tariff Walls Map (TWM), a large three-dimensional model of Europe on which international borders were represented by actual physical walls, the varying heights of which indicated average tariff restrictions imposed on traded goods by each European country. The TWM was one of the most widely debated maps of the 1920s and 1930s. Versions were exhibited in national parliaments, government ministries, chambers of commerce, and at international conferences across Europe and the United States, part of an ultimately unsuccessful campaign against economic protectionism. By depicting nation-states as volumetric spaces separated by physical barriers, the TWM contributed significantly to the idea of the ‘wall’ as an economic and geopolitical division.